Designing Geographic Inquiry: Preparing Secondary Students For Citizenship. Issue 6 (2nd November 2018) - Maddox, Lamont E.; Howell, James B.; Saye, John W.
Abstract: Social studies professionals advocate linking discipline-based content to citizenship learning goals. However, research suggests that students rarely encounter inquiry-based instruction in their geography coursework and have few opportunities to explore how geography impacts civic decision making. In this article, we present a problem-based geographic inquiry model that organizes geography instruction around civic problems that require ethical decision making. This model is being used as the basis for a lesson study professional development project called the Bridging Divides Project. A curricular exemplar on population change illustrates how the design process results in a product that supports learners in reasoning about a social issue.